Investigation Of Gold Wire Attachment During Led Encapsulation Process Using Computational Fluid Dynamic - Sahabarudin, Mohammad Nor Fikri (Universiti Sains Malaysia, 2021)
The aim of this research is to investigate the LED encapsulation method and the interaction of gold wire bonding with EMC. The encapsulation process is important because it serves as the LED’s first layer of protection. As noted in the preceding study, the encapsulating process has an impact on product quality. The brightness and colour of the light emitted will be affected by the encapsulant’s structure. As a result, one the element that can increase the product quality is the EMC which is chosen as an encapsulant because it offers a lot of advantages over other encapsulants. During the encapsulation process, another thing to consider is the dispensing inlet speed. The inlet speed will varying in this research to look at the effect on the pressure into the wire bond and identify the volume of fluid during the encapsulation process. The maximum pressure depends on the inlet velocity where the increase of inlet velocity, will be resulted in a decrease of pressure. Also, the greater inlet velocity shows a lower volume of fluid. ANSYS Fluent will be utilized to perform the encapsulation process virtually by utilizing VOF to stimulate the dispensing of EMC. An experiment was carried out to verify the theoretical result with experiment results.